Institutional Traps of Russia's Higher Education Nonlinear Development - Maria V.; Elena A. (National Research Mordova State University, 2018)
Introduction: the article deals with the problems arising in the Russian higher education system during its transformation. The topicality of this study lies in posing a problem of higher education development within the boundaries of a Russian macroregion. The objective of this article is to reveal barriers to the implementation of nonlinear processes in Russian higher education, which trigger the emergence of institutional traps and to determine the ways to avoid them. The purpose of this article is to identify barriers to the implementation of nonlinear processes in Russian higher education, which cause the emergence of institutional traps and determine the ways out of them. Materials and Methods: an institutional approach and the concept of non-linear models of higher education are the methodological basis of this research. The methods were developed by the research group of the Ural Federal University for sociological estimation of higher education transformation in the region. The procedure for selecting experts was realized according to the sociological methodology of I. E. Shteinberg (eight-window selection). Results: a summary analysis is made; inter-institutional interaction in terms of the "higher education - stakeholders" dyad is presented; the principal problematic areas are highlighted; and institutional traps preventing potential nonlinear development in Russian higher education are described. In the first problem zone, motivation traps, traps of formalisation/individualisation of the educational process, traps of intensification of the introduction of new information technologies in education and traps of unification of management were revealed. In the second problem area, traps of network interactions, traps of network interactions of higher education and employers, as well as traps of global/local orientation of universities were identified and analysed. Discussion and Conclusions: the authors outlined the most significant systemic ways for avoiding the described traps and present solutions for solving contradictions, which can be considered in terms of strategies and tactics for the management of reform processes in Russian universities. The proposed solutions are directly related to the activation of the main educational communities' potential. Within the framework of the project, the authors' method of sociological study of higher education transition to its nonlinear development within the boundaries of a particular macroregion was developed and tested.